HUBUNGAN ANTARA BEBAN KERJA FISIK DENGAN KELELAHAN KERJA PADA PEKERJA INDUSTRI PENGOLAHAN IKAN ASIN DI UD. X - Sherly Muzikha Yamaula; Ari Suwondo; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Fatigue is a subjective feeling accompanied by a decrease in efficiency and the needs. One factor that influences fatigue is work capacity. Salted fish processing industry workers use a lot of physical strength to work, if the physical workload received by workers increases, the workers will feel fatigued more quickly. The purpose of this study was to analyze the relationship between individual characteristics (age, sex, years of service, BMI, problems health) and physical workload with work fatigue. The type of this research was quantitative research, which was analytic observational with cross-sectional approach. The research instrument is to used the respondent's datasheet to observe individual characteristics, SNI 7269:2009 to measure physical workload based on calorie needs and the IFRC (Industrial Fatique Research Committee) Questionnaire to measure subjective work fatigue. The sampling technique used total sampling with population and sample in the study were 30 workers. Based on the statistical test with Fisher Exact, the results showed that there was no relationship between work fatique with age (p-value = 0.638), gender (p-value = 0.431), years of service (p-value = 1.000), BMI (p-value = 1.000), health problems (p-value = 0.070) and there is a relationship between work fatique with physical workload (p-value = 0.010). The suggestion for both company owners and workers is to pay attention to workers who are ex periencing fatique to take breaks or strecth muscles regularly every 2 hours.Keywords : Individual characteristics, physical workload, fatique